EVALUASI IMPLEMENTASI KEBIJAKAN JAMINAN KESEHATAN NASIONAL (JKN) DALAM MENINGKATKAN AKSES LAYANAN KESEHATAN MASYARAKAT DI INDONESIA - Gunawan Widjaja; Wagiman; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (Jurnal Kesehatan, 2025)
The National Health Insurance (JKN) is a strategic policy of the Indonesian government to improve access to health services for the entire population through a social insurance mechanism. This study aims to evaluate the implementation of the JKN policy in expanding access and improving the quality of health services in Indonesia. The research method used a literature review with an analysis of literature related to the implementation of JKN, supporting and inhibiting factors, and the impact on access to public health services. The findings indicate that JKN has successfully increased coverage, patient visits to healthcare facilities, and reduced financial barriers, particularly for vulnerable groups and the poor. However, challenges remain in the form of disparities in healthcare infrastructure, issues with inactive coverage, and quality disparities in services between urban and rural areas. The evaluation of JKN implementation underscores the need for policy updates, service innovations, and strengthened infrastructure and outreach to achieve the goal of Universal Health Coverage in a sustainable manner.